PRESPEKTIF HUKUM EKONOMI SYARIAH DALAM JUAL BELI SAHAM: PRESPEKTIF HUKUM EKONOMI SYARIAH DALAM JUAL BELI SAHAM - Septirani, Nabila; Febriyanti, Firda (Journal of Business Education and Social, 2022)
Shares are proof of ownership of a company, so the understanding of the process of buying and selling shares is the process of buying and selling shares on the stock exchange against a company that has been registered and is open for shares to be purchased by the public. This study uses a qualitative method because to explore the effect of the company's stock price on stock transactions in the Indonesian capital market. The results of the analysis show that buying and selling shares made by students only want to have savings in the form of shares for the future.